Pengaruh Perkembangan Sosial Emosional pada Perilaku Anak Usia Dini - Nurdelita Anggraini; Siska Astria Br Ginting; Wahyuni Dazura (Jurnal Hukum dan Demokrasi (JHD), 2023)
In early childhood, children experience a golden age, which is where children begin to be sensitive and sensitive to receive stimuli or stimuli. Social and emotional development in children is the emotional condition and ability of children to respond to their environment at an earlier age. Children's socio-emotional development aims to find out how they are. How to relate to other people, namely peers and people who are older than him. Be responsible for yourself and others and behave in a pro-social manner. Social Emotional Development in School Children. Socio-emotional development is increasingly understood as a crisis in children's development. This is because children are shaped through development in the learning process. Children's social development is strongly influenced by the process of parental care or guidance for children in introducing various aspects of social life or norms in society. Keyword: Socio-Emotional, Early Childhood